Target-based drug discovery through inversion of quantitative structure-drug-property relationships and molecular simulation: CA IX-sulphonamide complexes. (1st January 2018) - Žuvela, Petar; Liu, J. Jay; Yi, Myunggi; Pomastowski, Paweł P.; Sagandykova, Gulyaim; Belka, Mariusz; David, Jonathan; Bączek, Tomasz; Szafrański, Krzysztof; Żołnowska, Beata; Sławiński, Jarosław; Supuran, Claudiu T.; et al.
Abstract: In this work, a target-based drug screening method is proposed exploiting the synergy effect of ligand-based and structure-based computer-assisted drug design. The new method provides great flexibility in drug design and drug candidates with considerably lower risk in an efficient manner. As a model system, 45 sulphonamides (33 training, 12 testing ligands) in complex with carbonic anhydrase IX were used for development of quantitative structure-activity-lipophilicity (property)-relationships (QSPRs). For each ligand, nearly 5, 000 molecular descriptors were calculated, while lipophilicity (log k w ) and inhibitory activity (log K i ) were used as drug properties. Genetic algorithm-partial least squares (GA-PLS) provided a QSPR model with high prediction capability employing only seven molecular descriptors. As a proof-of-concept, optimal drug structure was obtained by inverting the model with respect to reference drug properties. 3509 ligands were ranked accordingly. Top 10 ligands were further validated through molecular docking. Large-scale MD simulations were performed to test the stability of structures of selected ligands obtained through docking complemented with biophysical experiments. Graphical Abstract: